Enhancing Nutritional Literacy Through Visual-Based Intervention in Elementary School - Josephira Carla Karenina; Farisa Azzahra Abidin Putri; Kahfita Kustiyaszepty Kirana; Atalik Jusuf Chadnezar; Talitha Salsabila Putri Gusna; Hanifah Mardhatillah; Muhammad Aqbil Rizky Z (International Journal of Science and Environment (IJSE), 2026)
Establishing healthy eating habits during childhood is crucial for long-term well-being, yet many elementary school students struggle to distinguish between nutritious and unhealthy food options. Traditional teaching methods often fail to engage young learners effectively on this topic. This study aims to explore the implementation and effectiveness of using flashcards as an interactive instructional tool to teach healthy and unhealthy food concepts to fifth-grade students at SDI Mohammad Hatta. A qualitative research design was employed to gain a deeper understanding of the learning process. Data were gathered through participatory classroom observations, semi-structured interviews with the students, and open-ended questionnaires administered to 25 fifth-grade participants. The collected data were analyzed using thematic analysis, focusing on student engagement, comprehension, and behavioral intentions. The findings revealed that the integration of flashcards significantly enhanced students' enthusiasm and active participation during the health lesson. The visual and gamified nature of flashcards helped students easily categorize various food items, improving their conceptual understanding of nutrition. Furthermore, qualitative responses indicated a positive shift in students' attitudes, with many expressing a strong intent to reduce junk food consumption and choose healthier snacks. In conclusion, flashcards serve as an effective, low-cost, and engaging pedagogical tool for nutrition education in elementary schools.